Building an Archaeology of Maya Urbanism : Planning and Flexibility in the American Tropics - Arnauld, Marie-Charlotte; Marken, Damien B., 1977- (Book collections on Project MUSE., 2023)
"Building an Archaeology of Maya Urbanism tears down misconceptions of Maya cities, building a new archaeology of Maya urbanism, highlighting the dynamics of an ancient civilization of the Americas. Exploring agents and processes that modified Maya urban landscapes, this volume highlights the flexibility of urbanization in the Maya lowlands"--